Nonhistaminergic and mechanical itch sensitization in atopic dermatitis. Issue 9 (September 2017) - Andersen, H. H.; Elberling, J.; Sølvsten, H.; Yosipovitch, G.; Arendt-Nielsen, L.
Abstract : Abstract: Chronic or episodic severe itch is recurrent in atopic dermatitis (AD). Nonhistaminergic itch pathways are suggested to dominate in AD itch, contributing to an "itch-scratch-itch cycle" that prolongs and worsens itch, pain, and skin lesions. We hypothesized that nonhistaminergic neuronal sensitization contributes to itch in AD. Hence, we compared sensitivity with thermal, mechanical, and chemical pruritic stimuli in patients with AD and controls. The study comprised 25 patients with AD with chronic itch and 25 healthy controls. Questionnaires on itch characteristics were administered, and sensory tests were conducted intralesionally, extralesionally, and in homologous areas of controls. Thermal and mechanical quantitative sensory testing (QST) as well as histamine and cowhage provocations were performed. Subsequently, hyperknesis and vasomotor reactivity were assessed. Average itch and associated pain among patients with AD were 60.7 ± 4.3 and 39.7 ± 5.2 (VAS0-100 ), respectively. Patients experienced significantly higher itch from cowhage both intralesionally and extralesionally compared with controls, whereas histamine-evoked itch intensity was not significantly different between groups. No group differences were found for thermal quantitative sensory testings or pain evoked by itch provocations. Patients had decreased mechanical detection thresholds intralesionally and increased mechanical pain sensitivity intralesionally and extralesionally. Lastly, patients exhibited intralesional and extralesional hyperknesis before chemical itch provocations and augmented hyperknesis after itch provocations. Increased itch in response to cowhage (but not histamine) suggests nonhistaminergic pathway-specific itch sensitization in AD, whereas increased susceptibility to mechanically evoked itch and pain, particularly intralesionally suggests sensitization of mechanosensitive circuitry not normally associated with itch. Drugs targeting the nonhistaminergic (PAR2/TRPA1 + ) itch pathway and itch sensitization are promising for treating AD itch. Abstract : Patients with atopic dermatitis with chronic itch reported increased itch, intralesionally and extralesionally, selectively in response to nonhistaminergic (cowhage) itch provocations and mechanical stimuli, suggesting neuronal sensitization.